Pengaruh mekanisme good corporate governance terhadap earning management pada perusahaan pertambangan yang terdaftar di bursa efek Indonesia (bei) - Adriantama, Bayu; Ratnawati, Vince; Nurmayanti, Poppy (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2014)
This study aims to prove the influence mechanism good corporategovernance against earning manqgement. This study is an empiriial study'on the effect of the mechanism good corporate governance against earning management in the mining company listed on the indonesian stock exciange period-200g-2-01I.The study was conducted on mining companies tisted on the indonesian stock exchange in the observation period 2009-20i1. Total sample of l6firms or 4g observations were selected through purposive sampling method. The data used are secondary data consisting of the data earning *orig"*nnt, kepemilikan institutional owned, the proportion of independent board, aid audit committee, Hypothesis testing is done using multiple regression.The results showed that the audit committee and the proportion of independent board no effect on earning management, while the institutional owned affect earning management.Keywords : Earning Management, Institutional owned, the proportion oJ' independent board, And audit committee